Large igneous provinces - Ernst, Richard E. (Cambridge : Cambridge University Press, 2014)
Large Igneous Provinces (LIPs) are intraplate magmatic events, involving volumes of mainly mafic magma upwards of 100,000 km3, and often above 1 million km3. They are linked to continental break-up, global environmental catastrophes, regional uplift and a variety of ore deposit types. In this up-to-date, fascinating book, leading expert Richard Ernst explores all aspects of LIPs, beginning by introducing their definition and essential characteristics. Topics covered include continental and oceanic LIPs; their origins, structures, and geochemistry; geological and environmental effects; association with silicic, carbonatite and kimberlite magmatism; and analogues of LIPs in the Archean, and on other planets. The book concludes with an assessment of LIPs' influence on natural resources such as mineral deposits, petroleum and aquifers. This is a one-stop resource for researchers and graduate students in a wide range of disciplines, including tectonics, igneous petrology, geochemistry, geophysics, Earth history, and planetary geology, and for mining industry professionals.
1. Introduction, definition, and general characteristics -- 2. Essential criteria: distinguishing LIP from non-LIP events -- 3. Continental flood basalts and volcanic rifted margins -- 4. Oceanic LIPs: oceanic plateaus and ocean basin flood basalts and their remnants through time -- 5. Plumbing system of LIPs -- 6. Archean LIPs -- 7. Planetary LIPs -- 8. Silicic (Felsic) LIPs -- 9. Links with carbonatites, kimberlites, and lamprophyres/lamproites -- 10. Geochemistry of LIPs -- 11. LIPs and topographic changes -- 12. LIPs and rifting -- 13. LIPs and links with contractional structures -- 14. LIPs and environmental catastrophes -- 15. Assessing the origin of LIPs -- 16. LIPs and implications for mineral, hydrocarbon and water resources.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Igneous rocks; Magmatism; Geodynamics; Earth (Planet) -- Mantle